Effect of Cyber Security on Networks Operations (A case study of Vodafone Ghana) - Kwadade-Cudjoe, Francis; Enoch, Yusuf Hyelnasinyi; Bunmi, Adelore Abosede (Archives of Business Research, 2019)
Several networks are being constructed every day, however, making sure the security of the network is not compromised, is very important. The study examined the effect of cyber security on networks operations using Vodafone Ghana as a case study. Using questionnaires, a convenience sampling technique was used to collect primary data, which was then subjected to series of processes and analyses. Vodafone Ghana has been checking the operational status of its implemented security measures, example, recording and maintaining access logs, and checking for unauthorized access to important information. However, it was revealed that the organization’s firewall system to protect undesired access to its servers from the outside world was not fully secured. As people may themselves be an attack vector through social engineering, everyone within an organization ultimately shares responsibility in ensuring best-practice cyber security processes are carried out. This requires staff education with regular updates to materials on hand, as new threats arise.